PENERAPAN MEDIA PEMBELAJARAN STIK ES KRIM UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI SD NEGERI 59 PALEMBANG - Bella Septianii; Bambang Hermansah; Imelda Ratih Ayu (STKIP Subang, 2024)
This study aims to determine whether the application of ice cream stick learning media can improve students' mathematics learning outcomes in multiplication material in grade II students of SD Negeri 59 Palembang. This research uses an experimental method, namely True Experiment Design. With Posttest-Only Control Design. The sample in this study was class IIA and IIB students totaling 55 students, a random sampling technique was taken. Based on the results of the hypothesis test conducted by this researcher using the t-test of two free samples (Independent sample t-test) obtained tcount results of 5.075 and ttable value = 1.674 with α = 0.05 and df = 5, then tcalculate > ttable so that H0 is rejected. From the hypothetical data, it can be concluded that there is an increase in the application of ice cream stick learning media to mathematics learning outcomes of grade II students of SD Negeri 59 Palembang.